The Effect of Modernization of Test Equipment, Analyst Competency and Primary Service on Customer Satisfaction and Its Implications on Customer Loyalty Center for Standardization of Services in the Pharmaceutical Chemical and Packaging Industry Services - Tua Marpaung, Mangala; Derriawan, Derriawan; Thalib, Supriadi (Dinasti Publisher, 2025)
The aim of this research is to determine and analyze the influence of modernization of test equipment, analyst competency and excellent service on customer satisfaction and its implications for customer loyalty at the Center for Service Standardization for the Pharmaceutical Chemical and Packaging Industry. This research category uses descriptive methods with a quantitative method approach. The sampling technique used purposive sampling with a total sample of 130 respondents. Data collection uses a questionnaire. The data analysis technique uses Structural Equation Modeling (SEM) analysis which is processed with Smart PLS 4.0. The results of the research prove that the variables of modernization of test equipment, analyst competency and excellent service influence customer satisfaction. Then the variables of analyst competency, excellent service and customer satisfaction influence customer loyalty. Meanwhile, modernization of test equipment has no effect on customer loyalty. Intervening test results prove that modernization of test equipment has no effect on customer loyalty through customer satisfaction. Meanwhile, analyst competency and excellent service influence customer loyalty through customer satisfaction. Likewise, complementary customer satisfaction is able to mediate the influence of analyst competence and excellent service on customer loyalty.